Seasonal changes dominate long-term variability of the urban air microbiome across space and time. (May 2021) - Núñez, Andrés; García, Ana M.; Moreno, Diego A.; Guantes, Raúl
Highlights: Airborne communities are characterized in a large urban area along two years. Seasonal changes prevail over local features to define their composition. A stable core of bacteria and fungi is present and dominant across space and time. Indicator taxa of seasonal periods are identified. Temperature and precipitation show the greatest influence on community variation. Abstract: Compared to soil or aquatic ecosystems, the atmosphere is still an underexplored environment for microbial diversity. In this study, we surveyed the composition, variability and sources of microbes (bacteria and fungi) in the near surface atmosphere of a highly populated area, spanning ~ 4, 000 Km 2 around the city center of Madrid (Spain), in different seasonal periods along two years. We found a core of abundant bacterial genera robust across space and time, most of soil origin, while fungi were more sensitive to environmental conditions. Microbial communities showed clear seasonal patterns driven by variability of environmental factors, mainly temperature and accumulated rain, while local sources played a minor role. We also identified taxa in both groups characteristic of seasonal periods, but not of specific sampling sites or plant coverage. The present study suggests that the near surface atmosphere of urban environments contains an ecosystem stable across relatively large spatial and temporal scales, with a rather homogenous composition, modulated by climatic variations. As such, it contributes to our understanding of the long-term changes associated to the human exposome in the air of highly populated areas.